Symbolic Systems or Real Solutions? Examining the Gap Between Digital Transparency and Corruption Prevention in Surabaya - Novinda Kurnia Ichsanti (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
The tendency of irregularities in the management of local government operational expenditures is one of the nodes prone to corruption that is often undetected by conventional control systems. This study aims to evaluate the effect of implementing an online-based whistleblowing system on the effectiveness of internal control and corruption prevention efforts in Surabaya City Government during the 2023-2024 fiscal year. This research adopts a quantitative approach with a descriptive-explanatory design, using secondary data collected from SPIP reports, APIP capabilities, corruption control effectiveness index (IEPK), MCP scores, and WBS system outputs. Analysis was conducted using descriptive statistical methods through SPSS, but inferential testing could not be carried out due to the limited number of observations (N=1) and the absence of data variation. The results show that although the WBS system has been actively used with a report completion rate of 61.2% and internal control indicators at the “Defined” level, procurement findings worth IDR 25.6 billion were still found by BPK. This finding indicates a gap between administrative performance and implementation reality. The implications of this study emphasize the need to strengthen the integration of data-based monitoring systems and reformulate more adaptive operational expenditure controls.